Isolation, Characterization, and Application of Bacteriophage LPSE1 Against Salmonella enterica in Ready to Eat (RTE) Foods - Huang, Chenxi; Virk, Safiullah M.; Shi, Jianchun; Zhou, Yang; Willias, Stephan P.; Morsy, Mohamed K.; Abdelnabby, Hazem E.; Liu, Jie; Wang, Xiaohong; Li, Jinquan (Frontiers in Microbiology, 2018)
Salmonella infection is an important foodborne consumer health concern that can be mitigated during food processing. Bacteriophage therapy imparts many advantages over conventional chemical preservatives including pathogen specificity, natural derivation, potency, and providing a high degree of safety. The objective of this study aimed to isolate and characterize a phage that effectively control Salmonella food contamination. Out of 35 isolated phages, LPSE1 demonstrated a broad Salmonella host range, robust lytic ability, extensive pH tolerance, and prolonged thermal stability. The capacity for phage LPSE1 to control Salmonella Enteritidis-ATCC13076 in milk, sausage, and lettuce was established. Incubation of LPSE1 at 28 °C in milk reduced recoverable Salmonella by approximately 1.44 log10 CFU/mL and 2.37 log10 CFU/mL at MOI of 1 and 100, respectively, as relative to the phage-excluded control. Upon administration of LPSE1 at an MOI of 1 in sausage, Salmonella count decreased 0.52 log10 at 28 °C. At MOI of 100, the count decreased 0.49 log10 at 4 °C. Incubation of LPSE1 on lettuce reduced recoverable Salmonella by 2.02 log10, 1.71 log10 and 1.45 log10 CFU/mL at an MOI of 1, 10 and 100, respectively, as relative to the negative control. Taken together, these findings establish LPSE1 as an effective weapon against human pathogenic Salmonella in various ready to eat (RTE) foods.